Enterogyrus spp. (Monogenea: Ancyrocephalinae) and Aeromonas jandaei co-infection associated with high mortality following transport stress in cultured Nile tilapia - Assane, Inácio Mateus [UNESP] (2021)
Monogenean infection of the internal organs is extremely rare when compared to external infections. This study describes mass mortality of Nile tilapia (Oreochromis niloticus L.) originating from co-infection with Enterogyrus spp. and Aeromonas jandaei following transport stress. The first fish deaths occurred on day 1 post-transport, while cumulative mortality reached approximately 90% by day 10 post-stocking. An atypical amount of pale (whitish) faeces floating on the surface of the water as well as typical clinical signs of motile Aeromonas septicemia, were reported. Adult monogeneans and countless eggs of monogeneans were found in the stomachs and the intestines of both moribund and dead fish, respectively. Two strains of A. jandaei were isolated from the kidneys. Scanning electron microscope microphotographs of the stomach revealed the presence of numerous monogeneans penetrating deep into the gastric tissue, and diffuse lesions filled with bacilliform bacteria. Histopathological examination showed multifocal eosinophilic infiltrate, gastric gland and epithelial necrosis with sloughed necrotic debris in the lumen. This is the first report of co-infection by Enterogyrus spp. and A. jandaei in Nile tilapia and the first report of Enterogyrus coronatus, Enterogyrus foratus, and Enterogyrus malbergi parasitizing tilapia in Brazil. These findings indicate that synergic co-infection by Monogenean stomach parasites (E. coronatus, E. foratus, and E. malbergi) and A. jandaei may induce high mortalities in tilapia following transport stress.